Two-dimensional metal-organic frameworks for gas sensing - Lister, AM (2024)
Metal-organic frameworks (MOFs) are attractive materials for use in gas sensing applications because of their porosity and high adsorptive site to mass ratios. Through synthesis of conductive MOFs, sensors that respond to analyte gases through a change in electrical resistance can be fabricated. However, the wide-scale use of MOFs as the functional element in electronic devices such as chemiresistors is limited by the absence of methods to reliably synthesise conductive MOFs uniformly and in situ on the desired substrates. In this thesis, methods of synthesising conductive MOFs to overcome these limitations are reported.